The constitutional court's role in consolidating democracy and reforming local election - Satriawan, Iwan; Mokhtar, Khairil Azmin (Constitutional Court of the Republic of Indonesia, 2015)
Within the same group as the USA and India Indonesia is one of the largest democracies in the world. After experiencing authoritarian rule for a few decades since its independence the country finally at the beginning of the twenty first century managed to chart along its new direction along democratic course and values. More than a decade has passed since the democratic transition begun yet the country still faces various constitutional dilemmas and enigmas. One of organs of the government which been entrusted to transform the country into a democratic nation is the Constitutional Court. The objective of this paper is to provide critical analyses of the role of the Constitutional Court of Indonesia in the process of consolidating local democracy. The scope of analysis is confined to a number of important cases heard by the court on local election disputes from the year 2008 to 2013. The rationale to focus on local election is because local government provides the second layer of government for this unitary country making the governance more democratic and more in touch with local population. The result of the study is the Constitutional Court through its decisions has created conducive political situation and has provided significant contributions in the process of consolidating local democracy. In spite of limited number of judges and short period of settlement to disputes brought before it the Court have settled all disputes regarding local elections without much delay and complaint. Nevertheless there are some areas that need to be addressed by the court to enhance its efficiency and effectiveness of the court. A few factors have been identified to be the cause of the problems namely problem of design of structure of the Court, extension of the scope of authority, period of settlement, over-dosis of authority and the breach of code of ethics of the judges.Thus it is recommended that in order to perpetuate the excellent achievements of the court the institution need to be strengthened by addressing the problems.